2017
DOI: 10.1111/jne.12512
|View full text |Cite
|
Sign up to set email alerts
|

Less is more: Caloric regulation of neurogenesis and adult brain function

Abstract: Calorie intake is essential for regulating normal physiological processes and is fundamental to maintaining life. Indeed, both extremes of calorie intake result in increased morbidity and mortality. In this review, we discuss the effect of calorie intake on adult brain function, with an emphasis on the beneficial effects of mild calorie restriction.Recent findings relating to the regenerative and protective effects of the gastrointestinal hormone, ghrelin, suggest that it may underlie the beneficial effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 171 publications
1
11
0
Order By: Relevance
“…However, most of these studies have compared energy-rich diets to normal lab chow, thus the observed effects might not primarily depend on sugar or fat itself but rather on increased calorie intake. The detrimental effect of high calorie intake on brain function and AHN has been shown before 48 . In the present study, we used isocaloric diets in order to ensure similar calorie intake in all groups.…”
Section: Discussionmentioning
confidence: 93%
“…However, most of these studies have compared energy-rich diets to normal lab chow, thus the observed effects might not primarily depend on sugar or fat itself but rather on increased calorie intake. The detrimental effect of high calorie intake on brain function and AHN has been shown before 48 . In the present study, we used isocaloric diets in order to ensure similar calorie intake in all groups.…”
Section: Discussionmentioning
confidence: 93%
“…Several good recent reviews are available, discussing the neurocognitive effects of bariatric surgery 150,151 and caloric restriction. 152,153 Our team also published a paper in 2015 discussing the benefits and drawbacks of surgical versus nonsurgical interventions for obesity and their potential effects on cognitive function. 154 The conclusions from that literature are similar to conclusions already discussed: decisions about what intervention to recommend need to be individually tailored, based on individual health and personality characteristics.…”
Section: Interventions: Weight Lossmentioning
confidence: 99%
“…Weight loss in its own right is associated with documented cognitive improvement. Several good recent reviews are available, discussing the neurocognitive effects of bariatric surgery and caloric restriction . Our team also published a paper in 2015 discussing the benefits and drawbacks of surgical versus nonsurgical interventions for obesity and their potential effects on cognitive function .…”
Section: Body Composition Vascular Function and Brain Healthmentioning
confidence: 99%
“…Many investigations in animal prototypes have demonstrated that reduced food intake leads to increased lifespan [71]. The other beneficial effects include improved gut microbiota composition and metabolome [72], reduced age-related methylation changes in the brain [73], increased adult neurogenesis [74,75], improved cognitive function [76][77][78], protection against age-related neurodegenerative disorders such as dementia [65,79].…”
Section: Intermittent Fasting As a Means To Combat Agingmentioning
confidence: 99%